Analisis Kualitas Pelayanan untuk Meningkatkan Kepuasan Konsumen: Studi Kasus Gold's Gym Bandung - Bernik, Merita (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2019)
Health is the most common thing and becomes the primary need of every human being. One way to keep us healthy is to diligently exercise. There are various kinds of sports that can be done, and there are also many facilities provided for sports. One of the facilities that can be utilized is the fitness center. One fitness center in Bandung has an increasing number of consumers and members. This shows the existence of consumer satisfaction, one of the variable to meet customer satisfaction is the existence of good quality service. The method used in this study is a descriptive method using primary data and secondary data, the data that has been obtained is then processed, analyzed and entered into the Cartesian diagram. The results obtained from the quality of services provided are in a fairly good category and many indicators are included in the B quadrant where quality is considered important as a factor supporting consumer satisfaction.